Rudolf Wagner in Maribor - Ivec, Anja (De musica disserenda, 2022)
A musician of German descent, Rudolf Wagner (1851–1915), was one of the key figures in Maribor՚s musical history in the second half of the nineteenth century and in the first two decades of the twentieth century. The present article reveals Wagner՚s polyvalent activity in the field of music and provides an outline of his life and career with significant turning points, focusing on his involvement in the Maribor cultural environment.